Multiculturalism, Identity and Difference Experiences of Culture Contact - Murdock, Elke.; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
Multicultural societies are a phenomenon that can be increasingly observed worldwide. This book focuses on the question of how individuals living within a multicultural society experience the meeting of cultures. Murdock combines both a thorough review of the theoretical body of research concerning multiculturalism and related concepts such as globalization, acculturation and biculturalism with specific empirical research evidence, providing new insights into factors which shape our openness towards a plurally composed society. Multiculturalism, Identity and Difference contains original research conducted within the 'natural laboratory' that multilingual, multicultural Luxembourg provides. This is a country where the foreign population makes up nearly half of the total population. In the era of globalization, culture contact is a daily occurrence and this book makes a contribution to the questions of if and how culture contact can be experienced as an opportunity rather than a threat by individuals. .
Introduction -- 1. Luxembourg - in a multicultural context -- 2. Multiculturalism in Context -- 3. The individual in a multicultural context -- 4. On being bicultural in a multicultural environment -- 5. On living in a multicultural environment -- 6. Final conclusions. .
Keywords: Ethnography; Cross Cultural Psychology